2022
DOI: 10.2337/db22-0033
|View full text |Cite
|
Sign up to set email alerts
|

Nontargeted and Targeted Metabolomic Profiling Reveals Novel Metabolite Biomarkers of Incident Diabetes in African Americans

Abstract: Nontargeted metabolomics methods have increased potential to identify new disease biomarkers, but assessments of the additive information provided in large human cohorts by these less biased techniques are limited. To diversify our knowledge of diabetes associated metabolites, we leveraged a method that measures 305 targeted or “known” and 2,342 nontargeted or “unknown” compounds in fasting plasma samples from 2,750 participants (315 incident cases) in the Jackson Heart Study (JHS)—a community cohort of self-i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Decades of epidemiology studies have established that elevated levels of circulating BCAAs and their metabolites are associated with insulin resistance and type 2 diabetes risk in populations of European ancestry (Felig et al, 1969 ; Gall et al, 2010 ; Guasch-Ferre et al, 2016 ; Huffman et al, 2009 ; Menni et al, 2013 ; Newgard et al, 2009 ; Shah et al, 2012 ; Stancakova et al, 2012 ; Tillin et al, 2015 ; Wang et al, 2011 ; Wurtz et al, 2012a , 2012b , 2013 ). These associations were recently confirmed in populations of Asian (Arany & Neinast, 2018 ; Chen et al, 2016 , 2019 ; Tai et al, 2010 ; Takashina et al, 2016 ; Tillin et al, 2015 ), African (Chen et al, 2022 ) and Mexican (Lee et al, 2016 ; Palmer et al, 2015 , 2018 ) ancestries. In this study, we observed in African Americans that increased levels of BCAA-related metabolites (isoleucine, 3-methyl-2-oxovalerate and 3-hydroxy-2-ethylpropionate in isoleucine metabolism; leucine, 4-methyl-2-oxopentanoate and isovalerylcarnitine in leucine metabolism; valine, 3-methyl-2-oxobutyrate and 3-hydroxyisobutyrate in valine metabolism; Supplementary Table 4a-f) were positively associated with basal measures of HOMA-IR but negatively associated with dynamic measures of S I , DI and S G .…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Decades of epidemiology studies have established that elevated levels of circulating BCAAs and their metabolites are associated with insulin resistance and type 2 diabetes risk in populations of European ancestry (Felig et al, 1969 ; Gall et al, 2010 ; Guasch-Ferre et al, 2016 ; Huffman et al, 2009 ; Menni et al, 2013 ; Newgard et al, 2009 ; Shah et al, 2012 ; Stancakova et al, 2012 ; Tillin et al, 2015 ; Wang et al, 2011 ; Wurtz et al, 2012a , 2012b , 2013 ). These associations were recently confirmed in populations of Asian (Arany & Neinast, 2018 ; Chen et al, 2016 , 2019 ; Tai et al, 2010 ; Takashina et al, 2016 ; Tillin et al, 2015 ), African (Chen et al, 2022 ) and Mexican (Lee et al, 2016 ; Palmer et al, 2015 , 2018 ) ancestries. In this study, we observed in African Americans that increased levels of BCAA-related metabolites (isoleucine, 3-methyl-2-oxovalerate and 3-hydroxy-2-ethylpropionate in isoleucine metabolism; leucine, 4-methyl-2-oxopentanoate and isovalerylcarnitine in leucine metabolism; valine, 3-methyl-2-oxobutyrate and 3-hydroxyisobutyrate in valine metabolism; Supplementary Table 4a-f) were positively associated with basal measures of HOMA-IR but negatively associated with dynamic measures of S I , DI and S G .…”
Section: Discussionmentioning
confidence: 82%
“…Circulating levels of glycine were lower in obese (Felig et al, 1969 ; Okekunle et al, 2017 ; Takashina et al, 2016 ; Yan et al, 2012 ) and insulin-resistant individuals (Ejaz et al, 2016 ; Gall et al, 2010 ; Newgard et al, 2009 ; Takashina et al, 2016 ) as compared to healthy individuals in populations of European and East Asian ancestries. Plasma glycine levels were also negatively associated with fasting glucose levels and type 2 diabetes risk (Chen et al, 2022 ; Ferrannini et al, 2013 ; Floegel et al, 2013 ; Guasch-Ferre et al, 2016 ; Newgard et al, 2009 ; Palmer et al, 2015 ; Svingen et al, 2016 ; Vangipurapu et al, 2019 ; Walford et al, 2016 ; Wang-Sattler et al, 2012 ). In concordance with the previous findings, we observed that the metabolites (glycine, N-acetylglycine or serine; Supplementary Table 4a-f) in the glycine, serine and threonine metabolism sub-pathway were positively associated with dynamic measures of S I and DI but negatively associated with basal measures of HOMA-IR and HOMA-B in IRAS-FS African Americans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations